Novel Genetic Variations in Acute Myeloid Leukemia in Pakistani Population - Shahid, Saba; Shakeel, Muhammad; Siddiqui, Saima; Ahmed, Shariq; Sohail, Misha; Khan, Ishtiaq Ahmad; Abid, Aiysha; Shamsi, Tahir (Frontiers in Genetics, 2020)
Acute Myeloid Leukemia (AML) is a hematological malignancy characterized by clonal expansion of blast cells that exhibits great genetic heterogeneity. In this study, we describe the mutational landscape and its clinico-pathological significance in 26 myeloid neoplasm patients from a South Asian population (Pakistan) by using ultra-deep targeted next-generation DNA sequencing of 54 genes (~5000X) and its subsequent bioinformatics analysis. The data analysis indicated novel non-silent somatic mutational events previously not reported in AML, including 9 nonsynonymous and 1 stop-gain mutations. Notably, two recurrent somatic nonsynonymous mutations i.e., STAG2 (causing p.L526F) and BCORL1 (p.A400V) were observed in 3 unrelated cases each. The BCOR was found having 3 independent nonsynonymous somatic mutations in three cases. Further, the SRSF2 with a protein truncating somatic mutation (p.Q88X) was observed for the first time in AML in this study. The prioritization of germline mutations with ClinVar, SIFT, Polyphen2, and Combined Annotation Dependent Depletion (CADD) highlighted 18 predicted deleterious/pathogenic mutations, including two recurrent deleterious mutations i.e., a novel heterozygous nonsynonymous SNV in GATA2 (p.T358P), and a frameshift insertion in NPM1 (p.L258fs), found in two unrelated cases each. The WT1 was observed with three independent potential detrimental germline mutations in three different cases. Collectively, non-silent somatic and/or germline mutations were observed in 23 (88.46%) of the cases (0.92 mutation per case). Furthermore, the pharmGKB database exploration showed a missense SNV rs1042522 in TP53, exhibiting decreased response to anti-cancer drugs, in 19 (73%) of the cases. This genomic profiling of AML provides deep insight into the disease pathophysiology. Identification of pharmacogenomics markers will help to adopt personalized approach for the management of AML patients in Pakistan.